Casual Store MY / Muhammad Fakhrur Razi Al Hafiy Jamiluddin - Jamiluddin, Muhammad Fakhrur Razi Al Hafiy (2021)
Casual Store MY is a new e-commerce that based in Facebook. Casual Store MY headquarter (HQ) is located in Senawang, Negeri Sembilan. This business is started in 19 April 2021. What my business do is selling a branded shoes and sneakers that have a good quality such as Nike and Adidas. We offer a good quality shoes with middle range price to our customers in between RM300-RM600. This business is for people that want or wish to have a good shoe with a reasonable price. My target market for this business is for student, worker, lecturer and anyone. Casual Store MY have made a good response and review, our customers is happy to have their sneakers with their quality that they get. They also willing to repeat their orders to have other new sneakers. Therefore, I hope Casual Store MY can sustain for a long time to serve a great shoes for our customers and I hope this business can be well known in Malaysia as a top sneakers seller.